Chemotherapy and cognition: International cognition and cancer task force recommendations for harmonising preclinical research. (September 2018) - Winocur, Gordon; Johnston, Ian; Castel, Hélène
Highlights: Standard tests and protocols are recommended for studying chemobrain in animals. Preclinical research is needed into non-cognitive factors (e.g., stress) in chemobrain. Animal models of chemobrain must take into account the effects of drugs and disease. Identifying biological and cognitive mechanisms is a priority for chemobrain research. Preclinical research has a role in developing treatment programs for chemobrain. Abstract: Cancer survivors who undergo chemotherapy for non-CNS tumours often report substantial cognitive disturbances that adversely affect quality of life, during and after treatment. The neurotoxic effects of anti-cancer drugs have been confirmed in clinical and pre-clinical research. Work with animals has also identified a range of factors and underlying mechanisms that contribute to chemotherapy-induced cognitive impairment. However, there is a continuing need to develop standard cognitive testing procedures for validation and comparison purposes, broaden the search for biological and neurochemical mechanisms, and develop improved animal models for investigating the combined effects of treatment, the disease, and other potential factors (e.g., age, stress). In this paper, a working group, formed under the auspices of the International Cognition and Cancer Task Force, reviews the state of pre-clinical research, formulates strategic priorities, and provides recommendations to guide animal research that meaningfully informs clinical investigations.